PPAR-α Agonist Fenofibrate Prevented Diabetic Nephropathy by Inhibiting M1 Macrophages via Improving Endothelial Cell Function in db/db Mice - Feng, Xiaomeng; Gao, Xia; Wang, Shuo; Huang, Mengxiu; Sun, Zhencheng; Dong, Hengbei; Yu, Haitian; Wang, Guang (Frontiers in Medicine, 2021)
Background: Diabetic nephropathy (DN) is one of the major diabetic microvascular complications, and macrophage polarization plays a key role in the development of DN. Endothelial cells regulate macrophage polarization. Peroxisome proliferator-activated receptor (PPAR)-α agonists were demonstrated to prevent DN and improve endothelial function. In this study, we aimed to investigate whether PPAR-α agonists prevented DN through regulating macrophage phenotype via improving endothelial cell function. Methods: Eight-week-old male C57BLKS/J db/m and db/db mice were given fenofibrate or 1% sodium carboxyl methylcellulose by gavage for 12 weeks. Results: Db/db mice presented higher urinary albumin-to-creatinine ratio (UACR) than db/m mice, and fenofibrate decreased UACR in db/db mice. Fibrosis and collagen I were elevated in db/db mouse kidneys compared with db/m mouse kidneys; however, they were decreased after fenofibrate treatment in db/db mouse kidneys. Apoptosis and cleaved caspase-3 were enhanced in db/db mouse kidneys compared to db/m mouse kidneys, while fenofibrate decreased them in db/db mouse kidneys. Db/db mice had a suppression of p-endothelial nitric oxide synthase (eNOS)/t-eNOS and nitric oxide (NO), and an increase of angiopoietin-2 and reactive oxygen species (ROS) in kidneys compared with db/m mice, and fenofibrate increased p-eNOS/t-eNOS and NO, and decreased angiopoietin-2 and ROS in db/db mouse kidneys. Hypoxia-inducible factor (HIF)-1α and Notch1 were promoted in db/db mouse kidneys compared with db/m mouse kidneys, and were reduced after fenofibrate treatment in db/db mouse kidneys. Furthermore, the immunofluorescence staining indicated that M1 macrophage recruitment was enhanced in db/db mouse kidneys compared to db/m mouse kidneys, and this was accompanied by a significant increase of tumor necrosis factor (TNF)-α and interleukin (IL)-1β in kidneys and in serum of db/db mice compared with db/m mice. However, fenofibrate inhibited the renal M1 macrophage recruitment and cytokines associated with M1 macrophages in db/db mice. Conclusions: Our study indicated that M1 macrophage recruitment due to the upregulated HIF-1α/Notch1 pathway induced by endothelial cell dysfunction involved in type 2 diabetic mouse renal injury, and PPAR-α agonist fenofibrate prevented DN by reducing M1 macrophage recruitment via inhibiting HIF-1α/Notch1 pathway regulated by endothelial cell function in type 2 diabetic mouse kidneys.